2007
DOI: 10.1007/s12011-007-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Zinc, Copper, Iron, Cobalt, Magnesium, and Selenium Elements in Children Diagnosed with Giardia Intestinalis and Enterobiosis Vermicularis in Hatay, Turkey

Abstract: The intestinal parasites are noted to be an important health problem in Turkey as similarly reported in the globe. The aim of this study was to investigate the changes in total content of essential elements, namely, zinc, iron, copper, cobalt, magnesium, and selenium, in children infected with intestinal parasites aged between 6 and 12 years inhabiting in Hatay Province, Turkey. These essential elements were measured in the children/patient who was positive for intestinal parasites, Giardia intestinalis and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…The association of giardiasis and enterobiasis with the malabsorption of zinc, copper, magnesium and vitamin B12 remains controversial. In several studies conducted about trace elements in giardiasis has shown a significant decrease in zinc levels while there was an obvious increase in copper levels [8,10,12,14]. However, in few reports there was no significant difference in serum levels of zinc, copper and magnesium elements between the two groups [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The association of giardiasis and enterobiasis with the malabsorption of zinc, copper, magnesium and vitamin B12 remains controversial. In several studies conducted about trace elements in giardiasis has shown a significant decrease in zinc levels while there was an obvious increase in copper levels [8,10,12,14]. However, in few reports there was no significant difference in serum levels of zinc, copper and magnesium elements between the two groups [21].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is especially vital for the immune system functions and its depletion is associated with decline in lymphocyte and thymus functions. Due to its role in immune system functions, zinc deficiencies make infants suffer from acute diarrhea [10]. Zinc deficiency is another increasing public health problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in different leukocytes may be due to the natural immune response generated against the infection and the greater increase in eosinophils is probably due to the fact that they are primarily involved in dealing with parasitic infections. Giardiasis is known to cause the zinc deficiency which results in decline in the number of lymphocytes 16,17 .…”
Section: Hemoglobin and Hematocrit Valuementioning
confidence: 99%